Hubungan Antara Karakteristik Ibu Bersalin Dengan Kejadian Bayi Berat Badan Lahir Rendah Di Rumah Sakit Dustira Cimahi Tahun 2021 - Elisa Situmorang; Ninda Rahmawati; Yuli Ratna Sari (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
Low birth weight babies is one of the causes of babies death around the word. In Indonesia, it is estimated that around 459.200-900.000 low birth weight babies are delivered each year. Low birth weight babies are hight related to fetal and neonatal mortality and morbidity. There are several influencing factors to low birth weight babies prevalence, one of them is the characteristics of the pregnant mother such as maternal age, education, and parity. This research has been conducted to find out the correlation between the characteristics of pregnant mother and low birth weight babies prevalence. The cross sectional approach to 170 mother who delivered low birth weight babies at Dustira Hospital during period of 2013. Statistical analysis used was Chi Square tes (α= 0,05). The result showed that the characteristics of pregnant mother based on age, education, and parity are likely to give birth to low weight babies. Suggestion made is to improve the health compaign, education, and counseling in order to reduce the prevalence of low birth weight babies.